Initiation of New Medication With an Actionable Pharmacogenetics-Based Prescribing Guideline in Discharged Hospital Patients in Finland - Kulla, Noora (My University, 2021)
OBJECTIVES. Purpose of this retrospective, register-based pharmacoepidemiologic study was to analyse post-discharge purchases of drugs with an actionable pharmacogenetics-based prescribing guideline with a patient cohort consisting of Finnish hospital patients. MATERIALS. Altogether 33 eligible actionable drugs were identified from prescribing guidelines compiled by the Clinical Pharmacogenetics Implementation Consortium. Hospital admission data, drug purchase data, and mortality data were utilized from 1.42 million eligible patients. METHODS. Each patient was followed from the first hospital admission to either surgical or internal medicine unit until the end of year 2016 or until death. Statistical analyses were descriptive on prevalence and incidence of drug purchases of individual drugs and related genes. Impact in Finnish population was studied by combining Finnish phenotype frequencies with drug incidence data. Differences in post-discharge drug purchases between the units was studied with Cox proportional-hazards model. RESULTS. Genes related to study drugs consisted of five drug-metabolizing CYP-genes, four other pharmacokinetic genes, one gene encoding a pharmacological drug target and three HLA-alleles altering to susceptibility to adverse effects. Most frequently purchased drugs in 2-year follow-up included common analgesics, proton pump inhibitors, cardiovascular drugs and a selective serotonin reuptake inhibitor. In 2-year follow-up, 60% of the patients purchased at least one drug, and drug purchases of 22% of the patients were associated to ≥ 2 different genes. DISCUSSION. Results provide significant new information of drug initiations in hospital discharged patients, which can be utilized in targeting pre-emptive pharmacogenetics testing to prevent drug adverse effects and rehospitalization. However, more studies are required on cost-effectiveness of pharmacogenetic testing.
Keywords: pharmacogenetics, pharmacoepidemiology, prescribing guideline